Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1974
DOI: 10.1007/bf02635151
|View full text |Cite
|
Sign up to set email alerts
|

Iron and phosphorus contents of soybean oil from normal and damaged beans

Abstract: Analyses of commercial crude soybean oils showed a highly significant correlation of 0.74 between free fatty acid and iron content. Poor flavor characteristics exhibited by finished oils extracted from damaged beans may be caused in part by a higher free fatty acid and related higher iron content in crude oils. Source of the increased iron appears to be both damaged beams and steel processing equipment. Crude oil from damaged beans is 2–10 times higher in iron than crude oil extracted from sound beans. Iron ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…As is well known, the phosphorus and iron contents of crude oils have always been a significant factor in vegetable oil refining. The poor quality of soybean oil by Evans et al (1974) was attributed to both high iron and high phosphorus contents. Similarly, Leibovitz and Ruckenstein (1981) reported that the stability of the oil was affected by traces of metals and phosphorus.…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, the phosphorus and iron contents of crude oils have always been a significant factor in vegetable oil refining. The poor quality of soybean oil by Evans et al (1974) was attributed to both high iron and high phosphorus contents. Similarly, Leibovitz and Ruckenstein (1981) reported that the stability of the oil was affected by traces of metals and phosphorus.…”
Section: Resultsmentioning
confidence: 99%
“…Failure to remove phospholipids has been reported to cause subsequent darkening during the steam refining process (Kock, 1980), whilst the residual trace metals will remain in the oil and catalyse oxidative deterioration (List el al., 1978a(List el al., , 1978b. It is known (Evans et al, 1974) that oils from damaged soyabeans contain increased FFA, high iron and non-hydratable phospholipids. In fact, the quality of oil extracted from soyabeans is characterized by analysis of iron, FFA, PV, phospholipid content, colour, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Metal ions are present in very low concentration in fully refined vegetable oils, e.g., 0.1-0.3 ppm of iron and 0.02-0.06 ppm of copper (20). To confirm this hypothesis, ferric and cupric ions (in the form of ferric ammonium sulfate and cupric acetate) were added to the natural and randomized corn oil, and their OSI values (h, at 100°C) were determined and are shown in Figure 5.…”
Section: Figmentioning
confidence: 99%